INDICATIONS OF CONSUMERS’ PROSUMER BEHAVIOUR ON THE FOOD MARKET - Marzena Lemanowicz (Polityki Europejskie, Finanse i Marketing)
The objective of this article was to identify examples of prosumer behaviour in the food market, to examine the degree of customer involvement and to measure the attitudes (opinions) of respondents regarding customer engagement in creation/improvement of a product. The most popular activities undertaken by consumers in the field of prosumption were selected and consumer involvement in various types of marketing campaigns organized by producers was determined. The survey was conducted among 320 respondents. The conducted research indicates consumer activity in the field of prosumption; however, respondents mainly manifest behaviour that do not require them to be very active. Sharing opinions on purchased food products is one of the manifestations of prosumer behaviour and these actions are undertaken with great frequency and willingness. The study also identified consumer participation in creating new products and improving existing ones. Over half of the respondents (64.4%) declared that they participated in these activities, however their participation is rare or very rare. In addition, consumers express positive opinions about the organization of such activities by companies and most of them believe that there are too few such activities on the market.